Impasse or mutation? Austerity and (de)financialisation of local governments in Britain. (2nd August 2021) - Dagdeviren, Hulya; Karwowski, Ewa
Abstract: Post crisis, local governments' (LGs) budgets have been drastically cut in Britain. Similar budgetary strains had serious consequences in the past, leading to major restructuring in LGs' functions. This paper interrogates the spatial dynamics of short-term municipal finances by putting into dialogue the political economy perspectives on financialisation with the economic geography literature on urban governance. Using data for over 400 municipal authorities in Britain, we examine locational underpinnings of changing financial practices with respect to spending cuts. We find that austerity increased risk and uncertainty for LGs. To preserve key services in such an environment, they resorted to short-term borrowing in breach of regulatory guidance. Effectively, an internal market for inter-council lending and borrowing has been created based on market principles in which LGs with surplus cash and reserves have extended credit to those with liquidity problems. On the asset side, the austerity programme forced them to embrace financial logics through a spectacular shift from cash and deposit holdings to investment in money market funds and credit extension as they have strived to generate as much income as possible to fund services at risk.